2014
DOI: 10.1002/fuce.201300089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Carbon from Okara and Application as Electrocatalyst Support

Abstract: Carbon materials derived from biomass are economical and simple. Here, a okara‐derived carbon (ODC) was prepared by carbonized cheap and abundant okara at 800 °C in N2 atmosphere. A high degree of graphitization, mesoporous structure and large specific surface area of ODC were proved by Raman spectroscopy, nitrogen adsorption–desorption isotherms, X‐ray diffraction, Fourier transform infrared spectra and scanning electron microscope. The ODC can be used as support of platinum nanoparticles, and the catalytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The elemental analysis revealed that by applying Fe species during pyrolysis, the pyridinic‐N‐oxide converted more to pyridinic‐N and graphitic‐N, and subsequently a higher ORR electroactivity was measured. The authors also previously introduced porous carbon from soybean okara as a catalyst support for Pt nanoparticles for the electrooxidation of methanol . Other reports suggested that Fe species mainly contribute to the decomposition and the graphitization of the soybeans.…”
Section: Lignocellulose Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…The elemental analysis revealed that by applying Fe species during pyrolysis, the pyridinic‐N‐oxide converted more to pyridinic‐N and graphitic‐N, and subsequently a higher ORR electroactivity was measured. The authors also previously introduced porous carbon from soybean okara as a catalyst support for Pt nanoparticles for the electrooxidation of methanol . Other reports suggested that Fe species mainly contribute to the decomposition and the graphitization of the soybeans.…”
Section: Lignocellulose Biomassmentioning
confidence: 99%
“…The authors also previously introduced porous carbon from soybean okara as a catalyst support for Pt nanoparticles for the electrooxidation of methanol. [147,148] Other reports suggested that Fe species mainly contribute to the decomposition and the graphitization of the soybeans. Then, the removal of soluble Fe-species by acid can assist the formation of the porous structure, while the graphitic layers encapsulate the remaining particles.…”
Section: Self-doped Electrocatalysts Using An Activation Agentmentioning
confidence: 99%
“…They may thus effectively replace the commercial carbon‐based catalysts in the electrocatalytic applications. Major electrocatalysis applications of these biomass‐derived carbons include methanol electrooxidation9196 and oxygen reduction reaction (ORR) 5. 97105…”
Section: Functionalization Of Carbonaceous Materials For Catalysismentioning
confidence: 99%
“…Okara has tremendous potential to generate affordable nitrogen-doped carbon. In our recent work [15,16], nitrogen-doped carbon derived from okara or soybean produced encouraging support effects for Pt particle-catalyzed methanol oxidation due to the presence of catalytic enhancing nitrogen species and its overall mesoporous structure. In our early work, we explored okaraderived carbon as a metal-free ORR electrocatalyst, but its ORR activity in both acid and alkaline medium was relatively low suggesting insufficient active sites on its surface.…”
Section: Introductionmentioning
confidence: 98%